Evaluation of motor oil residue and biosolid as micronutrient source in dark red latosol - Pigozzo, Ana Tereza Jordão (2008)
The potential of two organic residues was studied as micronutrient source in Dark Latosol (DL) in a greenhouse. The treatment consisted of a dose (19 t ha¹) of purified motor oil residue and sewage sludge, both neutralised by a 3:1 of CaO+MgO mixture. The maize (Zea mays L.) was the test’s reference plant. In the 30th day of seeding, the plant aerial parts were cut. These parts were dried at 60ºC until reaching a constant weight. Then they were weighed and grounded for later analysis. This analysis was undertaken after the nitric-perchloric digestion. The concentration values of the micronutrients in soil and plants were determined by atomic absorption spectometry. The results showed that the dry matter production was higher in sewage sludge use. Micronutrient levels in soil treated by sewage sludge and purified motor oil residue were higher than the in non treated soil. In the aerial parts of the maize plants, which were picked up from the soil treated by the biosolid residue, the micronutrients concentration of Cu, Mn, Fe and Zn were higher than the non treated one. Regarding the plants picked up from soil treated by purified motor oil residue, only the concentration of Fe and Zn was higher. Compared with biosolid, the oil residue was responsible for the highest C:N relation.